Morphological evaluation of new total etching and self etching adhesive system interfaces with dentin - Hegde, Mithra N (Medknow Publications & Media Pvt Ltd, 2012)
AIM: The purpose of this study is to evaluate the resin-dentin interface, quality of the hybrid layer of total-etching and self-etching adhesive systems under scanning electron microscopy (SEM). MATERIALS AND METHODS: Class V cavities were prepared in 40 extracted human molars. In Group I XP bond (Dentsply), in Group II Adper Single Bond II (3M ESPE), in Group III Adper Easy One (3M ESPE), and in Group IV Xeno V (Dentsply) were applied. Teeth were restored with resin composite, subjected to thermocycling, and sectioned in Buccolingual plane. The samples were demineralized using 6N HCl, for 30 sec, and deproteinized with 2.5% NaOCl for 10 min, gold sputtered, and viewed using a scanning electron microscope. RESULTS: Among the total-etch systems used, the XP Bond showed a clear, thick hybrid layer, with long resin tags and few voids. Among the self-etch adhesive systems, the Xeno V did not show a clearly recognizable hybrid layer, but there were no voids and continuous adaptation was seen with the dentin. CONCLUSION: The adaptation of self-etch adhesives to the resin-dentin interface was good without voids or separation of phases; showing a thin, continuous hybrid layer.